Research on psychological satisfaction of education work and learning of literary works - Wang, Yuanyuan (Hervormde teologiese studies, 2023)
The findings of this article reveal that the development of the independent learning model in the American literature curriculum positively impacts teachers' job psychological satisfaction. This study highlights the contribution of autonomous learning mode in empowering students' subjective status and enhancing their initiative, consequently reducing teachers' psychological pressure and improving their overall satisfaction with their work. Contribution The results of this study hold implications for scholars in the field, particularly those engaged in practical theology and religious educational studies.